Peran Guru Pendidikan Agama Islam dalam Membentuk Karakter Jujur Siswa Kelas IV di Sekolah Dasar Negeri 004 Bontang Selatan Tahun Pelajaran 2024/2025 - Saharani, Mardila (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
This study discusses the role of Islamic Religious Education (PAI) teachers in shaping the honest character of fourth-grade students at SDN 004 Bontang Selatan. This research aims to describe (1) the role of PAI teachers in enhancing the honest character of fourth-grade students at SDN 004 Bontang Selatan, and (2) the efforts to shape the character of fourth-grade students at SDN 004 Bontang Selatan. This research is a qualitative study with data collection techniques using observation, interviews, and documentation. The data analysis techniques used in this research include data reduction, data display, and drawing conclusions. The subjects of this research were the PAI teacher and fourth-grade students at SDN 004 Bontang Selatan. The results of the study indicate that PAI teachers have a strategic role as educators, mentors, role models, and facilitators in shaping the students’ honest character. Teachers instill the value of honesty through direct teaching, habituation, providing real examples, and giving positive reinforcement to students who demonstrate honest behavior. Additionally, school programs such as Quran recitation activities, Dhuha prayers, and flag ceremony speeches support the internalization of honesty values. The obstacles in shaping the honest character include the lack of parental support and external environmental influences. However, through collaboration between teachers, parents, and the school, the formation of honest character can be optimized.